Do Science and Religion Belong to Two Different Cultures? - Mahdi Golshani (حکمت اسرا, 2012)
There is a prevailing view today that science and religion have two radically different cultures. Some scientists hold that they are related to two independent cultures. Others believe that they overlap in some areas while according to some others they belong to two complementary cultures. This article tries to prove that science, as is generally understood, does not have a self-sufficient culture and shares common ground with religion in some aspects. Furthermore, science is dependent upon metaphysical assumptions and scientists deal with some ethical considerations. Therefore, science and religion, at least, do not belong to two entirely independent cultures, and in fact they can have an underlying common worldview.